Rab22a controls MHC‐I intracellular trafficking and antigen cross‐presentation by dendritic cells - Cebrian, Ignacio (EMBO Rep, 2016)
Cross‐presentation by MHC class I molecules allows the detection of exogenous antigens by CD8(+) T lymphocytes. This process is crucial to initiate cytotoxic immune responses against many pathogens (i.e., Toxoplasma gondii) and tumors. To achieve efficient cross‐presentation, dendritic cells (DCs) have specialized endocytic pathways; however, the molecular effectors involved are poorly understood. In this work, we identify the small GTPase Rab22a as a key regulator of MHC‐I trafficking and antigen cross‐presentation by DCs. Our results demonstrate that Rab22a is recruited to DC endosomes and phagosomes, as well as to the vacuole containing T. gondii parasites. The silencing of Rab22a expression did not affect the uptake of exogenous antigens or parasite invasion, but it drastically reduced the intracellular pool and the recycling of MHC‐I molecules. The knockdown of Rab22a also hampered the cross‐presentation of soluble, particulate and T. gondii‐associated antigens, but not the endogenous MHC‐I antigen presentation through the classical secretory pathway. Our findings provide compelling evidence that Rab22a plays a central role in the MHC‐I endocytic trafficking, which is crucial for efficient cross‐presentation by DCs.